First exercise reports of diabetes center in Turkey: Effects of exercise on metabolic parameters in patients with type-2 diabetes mellitus [Primi resoconti di allenamento da un centro per la cura del diabete in Turchia: Effetti dell’esercizio fisico sui parametri metabolici in pazienti con diabete mellito di tipo 2] - (:unkn) unknown (Edizioni Minerva Medica, 2021)
BACKGROUND: The current study aimed to show the efficacy of the exercise program performed by the type-2 diabetic patients in the exercise center related to the diabetes clinic. METHODS: This was a retrospective study, conducted on 77 (18-65 years old) diabetic patients who were attending the exercise center of the outpatient diabetes clinic. Patients who completed 3 months of supervised combined exercise program and having no chronic drug adjustment for 3 months at the beginning and during the exercise interval were recruited to the study. RESULTS: After 3 months, supervised combine exercise program, there were significant improvement of BMI (34.62 vs. 33.14 kg/m2, P<0.001), fat mass (34.95 vs. 33.83 kg, P<0.001), fasting blood glucose (124.59 vs. 117.39 mg/dL, P=0.015), HbA1c (6.74 vs. 6.45, P<0.001), and triglyceride levels (177.78 vs. 167.50 mg/dL, P=0.038). CONCLUSIONS: In conclusion, as a real-life data the supervised combine exercise program, performed in the exercise center of the diabetes clinic, significantly improved the metabolic parameters of the patients. We believe that diabetes clinics should include exercise centers, which are controlled by experts, to provide more qualified management for diabetic patients. Copyright © 2021 Edizioni Minerva Medica
Keywords: Body composition; Diabetes mellitus; Exercise